Research Trends on Parental Involvement in Inclusive Education and its Implications for Inclusive Education Programs: A Bibliometric Analysis - Kurniati, Diah; Zamroni, Edris; Utomo, Slamet; Lestari, Indah; Espejo Mirana, Ana (QALAMUNA: Jurnal Pendidikan, Sosial, dan Agama, 2025)
This article examines research trends on parental involvement in inclusive education in reputable databases. The method used is bibliometric analysis with the Biblioshiny application and the central database analyzed from scopus.com. The keywords used were "parental involvement" and "inclusive education" in research from 1975 to 2024. After the extraction process with only article publications in scientific journals, 170 publication data were obtained. The results of bibliometric analysis show that in nearly 50 years, the number of studies tends to be small—most research centers in the United States, with the most productive institution being the University of Minnesota. At the same time, the most productive researcher is Gabriella Pusztai, who has three publications. The primary reference journal is Early Child and Development Care. When viewed from keywords, child, parent, and parental involvement are the most dominant keywords researchers use. This provides a comprehensive picture of the development of parental involvement research. Furthermore, research is expected to be more contextualized with the socio-cultural conditions where the research is conducted to add to the diversity of research related to parental involvement, especially in inclusive education.